2017
DOI: 10.1016/j.jcrc.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ulinastatin combined with thymosin alpha1 on sepsis: A systematic review and meta-analysis of Chinese and Indian patients

Abstract: Treatment of UTI+Tα1 can suppress the production of proinflammatory cytokines, decrease the APACHE II score, shorten the duration of mechanical ventilation and vasopressor use, and improve the 28-day survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Recently, clinical trials in sepsis patients treated with UTI or UTI combined with thymosin α1 showed a survival benefit trend (Wu et al, 2013a; Karnad et al, 2014). Meanwhile, five meta-analysis of studies in sepsis patients either UTI administration alone or a combination of UTI and thymosin α1 have been published (Han et al, 2015; Li et al, 2015; Feng et al, 2016; Wang et al, 2016; Liu et al, 2017). Among these five meta-analysis, two meta-analysis (Feng et al, 2016; Liu et al, 2017) analyzed the effect of using UTI alone and no significant difference between UTI group and control group in the 28-day mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, clinical trials in sepsis patients treated with UTI or UTI combined with thymosin α1 showed a survival benefit trend (Wu et al, 2013a; Karnad et al, 2014). Meanwhile, five meta-analysis of studies in sepsis patients either UTI administration alone or a combination of UTI and thymosin α1 have been published (Han et al, 2015; Li et al, 2015; Feng et al, 2016; Wang et al, 2016; Liu et al, 2017). Among these five meta-analysis, two meta-analysis (Feng et al, 2016; Liu et al, 2017) analyzed the effect of using UTI alone and no significant difference between UTI group and control group in the 28-day mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, five meta-analysis of studies in sepsis patients either UTI administration alone or a combination of UTI and thymosin α1 have been published (Han et al, 2015; Li et al, 2015; Feng et al, 2016; Wang et al, 2016; Liu et al, 2017). Among these five meta-analysis, two meta-analysis (Feng et al, 2016; Liu et al, 2017) analyzed the effect of using UTI alone and no significant difference between UTI group and control group in the 28-day mortality. Given that the results of these two meta-analysis are based on subgroup analysis, which included the same two trials (Wu et al, 2013a; Karnad et al, 2014), it is difficult to prove the effect of UTI alone.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies suggest that high-dose ulinastatin achieves a comparable anti-inflammatory effect to glucocorticoids (Xu et al, 2018). In 2017, a meta-analysis of eight RCTs suggested that ulinastatin combined with thymosin α1 (Tα1) in sepsis patients suppressed pro-inflammatory factor production, reduced the Acute Physiology and Chronic Health Evaluation (APACHE) II score, shortened the durations of mechanical ventilation, and improved the 28-days survival rate (Liu et al, 2017). In addition, it does not induce immunosuppression and causes fewer side effects than glucocorticoids.…”
Section: Ulinastatinmentioning
confidence: 99%
“…Thymalfasin, also known as thymosin alpha-1, is a polypeptide hormone generated by thymic epithelial cells which can effectively increase the number of T cells, support T cell differentiation and maturation, and reduce apoptosis. Pathological observation of previous clinical studies [3] have con rmed the therapeutic e cacy of Thymalfasin in patients infected by hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunode ciency virus (HIV). Some current studies have demonstrated that thymosin drugs can increase the number of lymphocytes of COVID-19 patients and even reduce the mortality rate of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%